Impact of Workplace Bullying on Patient’s Quality-of-Care Services: A HealthCare Sector Perspective - Sabir, Irfan; Majid, Muhammad Bilal; Aslam , Muhammad Zia (Journal of Applied Research and Multidisciplinary Studies, 2023)
The current study aimed to measure the impact of nurse’s workplace bullying on patient’s quality of care with the mediating role of workplace deviance. The data was gathered from nurses in primary healthcare hospitals in Sahiwal and Faisalabad divisions of Punjab, Pakistan. The sample size was taken from a population comprising 1255 nurses through Krejcie and Morgan calculation formula and the final sample size was based on 254 nurses. Statistical analysis was performed through SPSS (v- 26) software. Constructs reliability and validity were analyzed through Cronbach’s alpha value which was above 0.90. The results confirmed that workplace bullying has a significant positive influence on workplace deviance and workplace deviance has significant negative influence on patient’s quality-of-care. Moreover, workplace bullying has a negative influence on patient’s quality-of-care and workplace deviance mediates the relationship between workplace bullying and patient’s quality-of-care.